Systematic Review of Nevus Counting and Reporting Methodologies in Contemporary Studies of the General Population - Jayasinghe, Dilki; Naranpanawa, Nathasha; Ashley, Daniel Paul; Ingvar, Åsa; Betz-Stablein, Brigid; Soyer, H. Peter; Janda, Monika (Dermatology Practical & Conceptual, 2024)
Introduction: Having many melanocytic nevi on the skin is a risk factor for melanoma. However, the reproducibility of nevus counts in previous studies is limited due to high inter- and intraobserver variation. Despite the introduction of a protocol for counting and reporting of nevi in 1990 by the International Agency for Research on Cancer (IARC), significant variations in nevus counting methods persist across studies. Objectives: We sought to review the variations in nevus counting and reporting methods, adherence and deviations from the IARC protocol, and the reproducibility of nevus counting studies. Methods: A systematic search of Embase, PubMed and Web of Science was conducted. The review was limited to nevus (>2 mm) counting studies of general population adults conducted between 2000 and 2022, and studies using skilled examiners. Results: Out of the 8 studies which were eligible for inclusion, none followed the IARC protocol. Three studies used a predefined criterion to count nevi. Five studies provided training for their observers. Three studies assessed the inter- or intraobserver variation using the correlation coefficient (>0.75), and 3 studies attempted to verify the validity and the reproducibility of the counts. There was little to no agreement in nevus counting and reporting procedures in the reviewed studies, and most studies did not report their procedures adequately. Conclusion: This review highlights the need for an easily accessible and feasible protocol for identification, counting and reporting of nevi, which also considers nevus counting from total-body imaging and automated nevus counts since these technologies are expected to become widely available for future studies.